The role of hromadas in the socio-economic development of regions (based on the example of Odesa Oblast) (Economics and region, 2024)
The article provides a comprehensive analysis of the socio-economic development of hromadas and enterprises in Odesa Oblast in recent years. The financial and economic performance of the enterprises is studied in the context of the economic stability of the region. The main socio-economic indicators of the development of hromadas in Odesa Oblast are analysed: the number of enterprises, the level of employment, remuneration and other financial indicators, with an emphasis on the problems and prospects of development. The paper proposes measures aimed at effectively addressing the problems of security, financial support, environmental rehabilitation, as well as socio-economic stimulation of hromadas and the region as a whole. The study will help to develop further steps to ensure sustainable development of the region and contribute to the formation of management strategies in the context of forecasting further directions of hromadas' development, attracting foreign investment and stimulating innovation.
Keywords: hromadas functioning; Odesa Oblast; economic analysis; regional development; development trends; socio-economic development